Wives and mistresses in eighteenth-century Scotland - Leneman, Leah (Women's history review, 1999)
Throughout the eighteenth century and beyond, under Scottish law mutual consent was the only thing required to constitute an irregular but legally binding marriage. If either party denied that a marriage existed it was open to the other to raise a declarator of marriage action before Edinburgh Commissary Court and provide evidence – for example, letters, or verbal acknowledgements – which would enable the court to decree that a legal marriage existed. Witnesses' perceptions of disputed relationships emerge from the records. Less than a third of the women whose cases were contested succeeded in proving a marriage, and accounts of cases in which women were decreed to be wives and those in which they were decreed to be mistresses reveal what a fine line there was between the two.